Sustainability of Sports in Marginalised Communities for People Living with HIV/ADIS (PLWHA) - Solihin, Akhmad Olih; Erida, Megia; Fahreza, Wildan Rifyal (Journal of Physical and Outdoor Education, 2024)
The current development in sport is the provision of socially motivated program through community-oriented or welfare or educational organizations. This   This research explores the development through sport of marginalized and disadvantaged people living with HIV/AIDS (PLWHA) by analyzing the results of a world street football event. This research focuses on the contribution of sports programs in developing social values for marginalized PLWHA in one of the social communities in Bandung City. The sociological impact of this research is to confirm that participation in sports programs can increase social value and self actualization, which in turn can provide positive value for PLWHA in obtaining employment, education and social environment. Evaluation and further research can be an input for the development of community sports, academics and sports policy in handling provision programs for marginalized people such as PLWHA.